PENGARUH INDEPENDENSI, KOMPETENSI DAN SKEPTISME PROFESIONAL TERHADAP KUALITAS AUDIT JUDGMENT - Putu Ayu Mahatma Dilla (UNHI Press, 2021)
This study aims to determine the effect of independence, competence and professional skepticism on the quality of audit judgment at the Financial Audit Board of Republic Indonesia (BPK RI) Representative of Bali Province. The sample that taken in this study was all auditors who worked at BPK RI Representatives of Bali Province. The sampling method in this study was using non-probability sampling with purposive sampling technique, totaling 60 auditors. The data collection method is done by using a questionnaire technique. The data analysis techniques used in this study include validity test, reliability test, descriptive statistical analysis, classical assumption test, multiple linear regression analysis, determination coefficient test (R2), F test and T test. The results of this study indicate that the variables are independence and competence. positive and significant effect on the quality of audit judgment, while the variable professional skepticism has no significant effect on the quality of audit judgment.